PROPOLIS SEBAGAI ALTERNATIF BAHAN ANTIKARIES GIGI - Hasan, A. E. Zainal; Artika, I Made; K, Popi A; Lasmiyanti, Metty (Sam Ratulangi University, 2011)
ABSTRACTZainal Hasan A. E. et al., 2011. Propolis as alternative additive anti-cariesPeriodontal disease included dental caries still the major problem in the world. Usually commercial tooth pastecontains fluoride which has an important role to prevent tooth from damage. Contain fluoride overdose causedfluorosis, bone damage and anemia. Therefore, the propolis was being tested as alternative additive anti cariesto prevent the growth of cariogenics bacteria (Streptococcus mutans). This research studied propolis activityantibacterial and the minimum inhibitory concentration (MIC) of propolis against S. mutans.Ethanolic extract of propolis (EEP) contained various bioactive compound such as flavonoid, tannine, alkaloid,triterpenoid and saponin based on phytochemistry analyses. The extract effectivities are 96.5% relative to thepropolis X, 41.04% relative to amphicillin 10 mg/ml and 240.57% relative to NaF 3000 ppm. The MIC of theextract is 3.13%. Therefore, propolis extract can be used asa additive anti caries element in tooth paste.Statistical analyses showed that 100% EEP, X propolis and amphicillin 10 mg/ml had the ability to decrease S.mutans colonyKeywords : propolis, anti-caries, ethanolic extract